Uses and Misuses of Typology in Indo-European Lingistics - Matasović, Ranko (Array, 2000)
It is argued that typology has so far been mostly misused in Indo-European linguistics, and that theories claiming that PIE had active or ergative clause alignment are not based on solid arguments.